Relaksasi Otot Progresif Menurunkan Tekanan Darah Pasien Hipertensi - Muhammad Basri; Sitti Rahmatia; Baharuddin K; Nur Afni Oktaviani Akbar (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Hypertension or high blood pressure is still a health problem experienced by the world's population, especially in Indonesia. Hypertension or high blood pressure is an increase in systolic blood pressure 140 mmHg and diastolic blood pressure 90 mmHg when examined twice within 5 minutes in a calm state. One way to reduce blood pressure in hypertensive patients is to relax muscles progressively. Objective: This study aims to explain progressive muscle relaxation in lowering blood pressure in hypertensive patients. Methods: The retrieval and data collection method are carried out through library research by tracing the results of scientific publications from 2017-2022 through the Google Scholar, Pubmed, and Researchgate databases. Results: Progressive muscle relaxation can be done continuously at least twice daily for 25-30 minutes. Conclusion: Progressive muscle relaxation should be done correctly with the correct sequence, movement, and focus so that individuals who do progressive muscle relaxation feel relaxed. Progressive muscle relaxation can be done independently or in combination with other non-pharmacological techniques